The digital social partner: Preschool children display stronger imitative tendency in screen‐based than live learning. Issue 4 (26th August 2021) - Fong, Frankie T. K.; Imuta, Kana; Redshaw, Jonathan; Nielsen, Mark
Abstract: We report on a study in which 4‐ to 6‐year‐olds were presented with a sticker‐retrieval task and asked to choose between one of two tools they could use to complete it. One of the tools was efficient but verbally identified to be the one that "nobody" uses; the other option was less efficient, but children were told it was the tool that "everybody" uses. Children learned about the level of efficiency and normative‐use of each tool option through one of three presentation mediums: (i) in a face‐to‐face, live demonstration; (ii) via a demonstration video presented on a laptop; or (iii) via a demonstration video presented onto a small whiteboard from a mini‐projector. Intriguingly, children's normative tendency varied depending on the presentation medium. Specifically, children who viewed the demonstration video on a laptop displayed a stronger tendency to employ the inefficient option tool that "everybody" uses, whereas children who were presented the demonstration live or via a demonstration video using a mini‐projector were more inclined toward the efficient option that "nobody" uses. We contend that children may now be perceiving digital screens using a social lens, where children's prior experience with screen devices alters the way they interpret and respond to information presented through this medium. This study affords novel insights into how children may treat digital screens as their modern social learning partner, and raises important questions about the credibility and social relevance of digital platforms in the current generation. Abstract : 4‐ to 6‐year‐olds were presented with two sticker‐retrieval tasks. For each task, they were asked to choose between an efficient option (a) and an inefficient option (b), with the latter being verbally identified as the normative option. Children who viewed the demonstration video on a laptop (E1) displayed a stronger tendency to employ the inefficient option, than children who were presented the demonstration live (E2) or via a demonstration video using a mini‐projector (E3). We contend that children may now be perceiving digital screens using a social lens, where children's prior experience with screen devices alters the way they interpret and respond to information presented through this medium.